Canibalismo em larvas de matrinxã, Brycon cephalus, após imersão dos ovos à diferentes concentrações de triiodotironina (T3) - Gervasio Leonardo, Antonio Fernando; Hoshiba, Marcio Aquio [UNESP]; Senhorini, Jose Augusto; Urbinati, Elisabeth Criscuolo [UNESP] (Inst Pesca, 2008)
The present work evaluated larvae cannibalism of matrinxa, Brycon cephalus, originated from eggs exposed to triiodothyronine, in the period of 36 to 72 hours after hatching. Observed parameters were: weight and length of larvae, stomach content, presence of cannibalism and type of attacks. This study was carried out at Centro de Pesquisa e Gestao de Recursos Pesqueiros Continentais (CEPTA/IBAMA), Pirassununga-SP, in November 2004. Three females were hormonally induced to spawn and pooled oocytes were fertilized and separated into four batches that constituted the treatments: L-1 (control - water); L-2 (0.01 ppm T-3); L-3 (0.05 ppm T-3) and L-4 (0.1 ppm T-3). Eggs were exposed during 15 minutes to water or to solutions containing the different concentrations of T3. Eggs were distributed in 12 conic incubators (60 L), with three replicates per treatment. There was stocked 500 mL of eggs per incubator and hatched larvae were counted. Samples of 30 larvae per treatment were colleted during occurrence of cannibalism (36, 48, 60 and 72 hours post hatching). Predator larvae (with rests of larvae in the stomach) were 50% of the total number of larvae and they presented weight 50% higher compared to that of non predator larvae (without rests of larvae in the stomach) and 9% higher regarding length. Coefficient of variation of weight and length did not differ among treatments, showing similarity in relation to the size. The stomach content revealed that cannibalism occurred in around 50-60 % of larvae, regardless the exposure to the triiodothyronine, and attacks were characterized as head-tail and tail-head attacks.
Cannibalism of matrinxa, Brycon cephalus, larvae after immersion of eggs to different triiodothyronine (t-3) concentration
Keywords: Larviculture; Brycon cephalus; Thyroid hormones; attacks